Operator dermal exposure and protection provided by personal protective equipment and working coveralls during mixing/loading, application and sprayer cleaning in vineyards. Issue 2 (3rd April 2017) - Thouvenin, Isabelle; Bouneb, Françoise; Mercier, Thierry
Abstract : The efficiency of a working coverall combined with personal protective equipment to protect operators against dermal exposure to plant protection products under field conditions was studied. Operators wore a non-certified water-repellent finish polyester/cotton coverall plus a certified gown during the mixing/loading and the cleaning phases. Insecticide foliar application to a vineyard was selected as the exposure scenario. The overall dermal residue levels measured in this study were in the range of data recently collected in Europe. The water-repellent finish working coverall reduced body exposure by a factor of approximately 95%. Wearing a Category III Type 3 partial body gown during mixing/loading and cleaning of the application equipment led to a further protective effect of 98.7%. The combination of a water-repellent finish working coverall and partial body protection during specific tasks provided satisfactory levels of protection and can be considered as suitable protection for the conditions of use studied.